Analisis kemampuan pemecahan masalah matematika siswa SMP berdasarkan tahapan polya ditinjau dari adversity quotient - Nababan, Rahel Juliana (Rekarta Academic Publisher, 2018)
This study aimed to describe the skill of junior high school studentâs mathematical problem solving based on the type of AQ. This study is a qualitative-descriptive study. Subjects in this study are students of class VIIIB in SMP Kristen Satya Wacana academic year of 2018/2019, that is climber, camper, and quitter. The data in this study were obtained through three methods, that was questionnaires, test and interview. The results showed that the skill of climber student in understanding problems were mentioning all the information in the problem completely and reiterated the given problem using his own language, and making a plan first to solve the problems, making an alternative solution, writing down the steps to resolve in a coherent and clear answer, and re-examining the solution. Skill of camper student in understanding  problems were not mentioning all the information in the problems and reiterated the given problem by using his own language, and planning first the troubleshooting steps, writing less detailed steps to resolve, and not checking back the solution. Skill of quitter student in understanding problems were not writing down the information in complete and  reiterated the given problem by using his own language, and having a difficulty in planning steps to solve the problems, having a difficulty in writing the completion of the steps, and not re-examining the solution